Early experience using vacuum-assisted closure for managing soft tissue injuries in open type IIIB tibial fractures, a non-randomised controlled trial from a North African level one trauma centre - Albair Malaka Hakim; Ahmed A Khalifa; Hossam Abubeih; Kamal A El-Gafary; Osama Farouk (Journal of Orthopaedics, Trauma and Rehabilitation)
Purpose: The primary objective was to investigate our early results of using vacuum-assisted closure (VAC) for wound management in patients with open IIIB tibial fractures and compare the results with a group subjected to conventional daily dressing. Methods: A prospective non-randomised clinical trial (NRCT) with a parallel design and allocation ratio of 1:1 was conducted after obtaining ethical committee approval. Forty skeletally mature patients with unilateral type IIIB open tibia fractures were included over two years, starting from April 2019. In group A, patients were treated with VAC, which was changed every four days if needed, and in group B, patients had daily conventional dressings. Results: Both groups had no differences in the basic demographic, comorbidities, injury mechanism, and associated injuries. The need for secondary debridement surgeries was significantly lower in Group A than in Group B, 1 ± 0.50 versus 2.50 ± 0.85, respectively ( P  < 0.001). The time till definitive coverage was significantly lower in Group A than in Group B, 12.22 ± 2.90 versus 23.56 ± 8.68 (days); P  < 0.001. All coverage procedures succeeded in Group A, while four (20%) failed in Group B, P  = 0.04. Infection was higher in Group B, with six (30%) patients compared to one (5%) in Group A, P  = 0.01. Conclusion: Reports on VAC's role in managing severe open fracture wounds are rare in our area, and the initial results we obtained are encouraging, with lower infection rates and less cumbersome reconstruction procedures; however, further evaluation of the procedure's cost-effectiveness is mandatory.